P36 Validating pulmonary arterial hypertension-associated genomic mutations of EIF2AK4: when is a variant pathogenic?. (11th November 2022) - Emanuelli, G; Morrell, NW; Marciniak, SJ
Abstract : Pulmonary arterial hypertension (PAH) is a fatal condition affecting young adults in which aberrant pulmonary vascular remodelling raises artery pressures causing right heart failure. It is frequently caused by mutations of the type II BMP receptor (BMPR2), however additional modifying factors exist. Mutations in the EIF2AK4 gene, encoding the kinase GCN2 have also been associated with PAH but the mechanisms remain elusive. In healthy individuals, active GCN2 selectively phosphorylates eIF2α to trigger the Integrated Stress Response (ISR) which temporarily attenuates protein synthesis while rescuing cellular amino acid uptake. In pulmonary veno-occlusive disease (PVOD), a rare and more aggressive subtype of PAH, biallelic mutations of EIF2AK4 have been found to be causative. With no effective treatments apart from lung transplantation, death occurs in 72% of patients within the first year after diagnosis. Approximately 70 potentially pathogenic EIF2AK4 alleles have been reported in patients with PAH. Forty percent of these are missense variants with unknown (if any) effects on GCN2 function and so are variants of uncertain significance (VUS). Confirming the pathogenicity of a VUS is important to families, as it is necessary to cascade genetic testing to potentially at-risk relatives. Strategies to predict the pathogenicity and severity of genetic variants have been restricted to computational methods. These approaches rely on the degree of evolutionary conservation of the mutated residue or on modelling algorithms that predict differences in folding free energies. Such computational strategies, although useful in prioritising the study of variants, are not foolproof and require experimental validation. To address this, we developed a protocol for the assessment of EIF2AK4 VUSs. We express patient-specific variants in GCN2-deleted cells and assay protein stability and activity. In doing so, we can sub-classify variants as non-pathogenic, destabilised or kinase-dead. In addition to providing benefits for genetic testing immediately, this may drive the development of allele-specific personalised therapies. Please refer to page A213 for declarations of interest related to this abstract.